"A Pleasant and Tidy Arrangement"1: Housing Development and Economies of Segregation in Mtwara, Tanganyika, 1949-1954. (July 2018) - Kelly, Chau Johnsen
In 1949, the colonial government of Tanganyika began clearing land for a model urban landscape in a remote district. This city was built as one facet of the Tanganyika Groundnut Scheme, a development debacle that cost the British taxpayer £36 million and yielded few benefits. The most significant outcome of the Scheme was the development of the port city of Mtwara, which held some promise as a model colonial space. As such, the urban development of Mtwara reveals how colonial officials used urban planning to alter a region's economic productivity from a pre-industrial system to one directly linked to state power. Town planning was a strategic device to marginalize existing African communities and reconfigure power dynamics in an African landscape. This article examines how segregation was performed late in the colonial project, how social economies were reconfigured, and how housing development was rooted in entrenched views about rights and citizenship.